2021
DOI: 10.18409/ispiv.v1i1.80
|View full text |Cite
|
Sign up to set email alerts
|

On the uncertainty of defocus methods for 3D particle tracking velocimetry

Abstract: Defocus methods have become more and more popular for the estimation of the 3D position of particles in flows (Cierpka and Kahler, 2011; Rossi and K ¨ ahler, 2014). Typically the depth positions of particles are ¨ determined by the defocused particle images using image processing algorithms. As these methods allow the determination of all components of the velocity vector in a volume using only a single optical access and a single camera, they are often used in, but not limited to microfluidics. Since almost n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…With the rise of machine learning in computer vision and neural networks in particular, new methods for particle detection based on convolutional neural networks (CNN) [20,21] emerged in the DPTV/APTV community. Cierpka et al [22] demonstrated the applicability of Faster R-CNN [23] for particle detection in APTV. Franchini and Krevor [24] demonstrated an improved detection rate on overlapping particle images for a CNN-based model in APTV.…”
Section: Introductionmentioning
confidence: 99%
“…With the rise of machine learning in computer vision and neural networks in particular, new methods for particle detection based on convolutional neural networks (CNN) [20,21] emerged in the DPTV/APTV community. Cierpka et al [22] demonstrated the applicability of Faster R-CNN [23] for particle detection in APTV. Franchini and Krevor [24] demonstrated an improved detection rate on overlapping particle images for a CNN-based model in APTV.…”
Section: Introductionmentioning
confidence: 99%